NUCLEAR MICRO-REACTOR THERMAL ANALYSIS METHODOLOGY - Alex Constantin Sumanriu; Maria Oprisescu; Catalin Gheorghe Amza (Nonconventional Technologies Review, 2024)
This paper presents a methodology for the thermal analysis of our design of a nuclear micro-reactor, addressing the challenges of efficient heat management and safety in compact reactor designs. We introduce an approach that integrates computational fluid dynamics and thermal-hydraulic simulation, for the constraints and operational parameters of micro-reactors.  Our methodology highlights the factors that influence micro-reactor thermal performance, including coolant flow rate, temperature, geometric configuration, and heat transfer. We further explore the implications of our findings for reactor design, emphasizing the importance of thermal efficiency and safety margins in the development of advanced nuclear micro-reactors. Significantly, our work not only contributes to the optimization of micro-reactor designs but also provides a framework for future research in nuclear reactor thermal analysis. The implications of our study extend to the broader field of nuclear engineering, offering valuable insights into the safe, efficient, and sustainable deployment of nuclear micro-reactors.